EFEKTIFITAS MEDIA AUDIO DAN MEDIA LEAFLET BRAILLE TERHADAP PENGETAHUAN MEMELIHARA KEBERSIHAN GIGI DAN MULUT PADA ANAK-ANAK TUNANETRA - Erni Mardiati; Salikun Salikun; Kurnia Aprianti (Jurnal Kesehatan Gigi, 2018)
TITLETHE EFFECTIVENESS OF AUDIO MEDIA AND BRAILLE LEAFLET MEDIA ON THE KNOWLEDGE OF MAINTAINING ORAL HYGIENE AMONG BLIND CHILDRENABSTRACTDental health education is a learning process that is targeted at individuals and groups of people to achieve the degree of community dental health as high. The blind children in need of media to improve oral health knowledge. Blind children take advantage of the sense of touch and hearing as a substitute for the sense of sight in the learning process. The purpose of research is to see the level of knowledge of how the maintenance of oral hygiene in blind children with education using audio media and leaflet braille media. This study design using interventional analytic sample were 24 children with visual impairment in SLB N Semarang using audio media and media leaflet braille. Each group was given individual counseling media, namely audio media and media leaflet braille. Before the students were given about counseling, pretest then given counseling. After being given counseling students were given the posttest.The data have been analyzed using statistical test o Wilcoxon Test and Mann Whitney Test.Statistical test with Wilcoxon Test showed a significant difference with p-value of 0.003 between before and after counseling with audio media. There is a significant difference p-value of 0.002 before and after counseling with counseling leaflet braille media. The study shows the differences in the level of knowledge with a p-value of 0.001 between groups of media education with audio and leaflet braille media. According to the results Mann Whitney Test can be concluded the levels of knowledge of how the maintenance of dental and oral hygiene in children with visual impairment in which audio media outreach is increased knowledge than leaflet braille media education.Key words : promotion, audio media,leaflet braille media